1995
DOI: 10.1152/ajprenal.1995.269.6.f854
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro osmotic regulation of HSP-70 and prostaglandin synthase gene expression in kidney cells

Abstract: As a function of the urinary concentrating mechanism, the cells of the renal medulla are exposed to elevated and constantly varying osmolalities and adapt to this environment by selectively expressing certain mRNAs. We evaluated the expression and regulation of two RNAs that may be important in adaptation of rental medullary cells to hyperosmolality. We demonstrate selective, modulated expression in the renal medulla of heat shock protein HSP-70 mRNA and prostaglandin synthase-1 mRNA, with the abundance of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 0 publications
3
41
1
Order By: Relevance
“…In this context, Cox inhibitors have been shown to reduce the survival of IMCD cells kept under high osmolarities in culture, pointing to cellular protective effects of Cox-derived prostanoids (24). It has been demonstrated that an increase of papillary tonicity by dehydration increases not only Cox-2 (22-24) but also Cox-1 expression in the inner medulla of rats (23). Cell culture experiments with IMCD cells confirmed a stimulation of Cox-2 expression by high osmolarity mediated by ERK, JNK-2, and p38 kinases (24).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, Cox inhibitors have been shown to reduce the survival of IMCD cells kept under high osmolarities in culture, pointing to cellular protective effects of Cox-derived prostanoids (24). It has been demonstrated that an increase of papillary tonicity by dehydration increases not only Cox-2 (22-24) but also Cox-1 expression in the inner medulla of rats (23). Cell culture experiments with IMCD cells confirmed a stimulation of Cox-2 expression by high osmolarity mediated by ERK, JNK-2, and p38 kinases (24).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Cox-2 in the inner medulla has already been shown to be influenced by the osmolarity (22)(23)(24), and we found in this study that furosemide reduced the osmolarity of the urine from 1550 Ϯ 108 mosmol/L in untreated to 480 Ϯ 33 mosmol/L in furosemide-treated rats; we, therefore, considered the possibility that it may be the low osmolarity that causes the downregulation of Cox-1 and to a lesser extent of Cox-2 expression in the inner medulla.…”
Section: Influence Of Furosemide Treatment On Pge 2 Concentrationmentioning
confidence: 99%
See 3 more Smart Citations